Correlation of Human Telomerase Reverse Transcriptase Promoter (hTERT) Gene Methylation and Ageing - Nihayah, Silviatun; Wening Sari; Yusnita, Yusnita; Intan Razari; Kinasih Prayuni; Utomo, Ahmad Rusdan Handoyo (Universitas Negeri Semarang, 2025)
Promoter methylation of the hTERT gene in blood DNA has been proposed to be an epigenetic molecular clock because it is negatively correlated with ageing. Saliva is an alternative source of DNA because it contains buccal cells. Currently, the correlation of hTERT promoter methylation and ageing using saliva is not known. This study aimed to determine: first, the correlation between hTERT promoter methylation and ageing in saliva, as a source of non-invasive DNA sampling, instead of blood was determined. Second, the influence of sex on the methylation of the hTERT promoter in ageing was evaluated. A cross-sectional study design was used, and 119 subjects were recruited, consisting of 25 children (1-5 y.o), 42 teens (17-19 y.o), 16 adults (20-50 y.o), and 36 elderly (60 to 84 y.o). Promoter methylation of the hTERT of extracted DNA was determined using the MSRE (methyl-specific restriction enzyme) method. The relationship between age and the percentage of hTERT methylation was assessed using the Pearson test. The percentage of hTERT methylation in saliva DNA was negatively correlated with age r= -0.4305 (p-value <0.05). Negative correlation was also found in men (r= -0.376) and women (r=-0.43). Negative correlation between hTERT and ageing has been confirmed in saliva as a noninvasive sampling method. The benefit of this research in ethical and social considerations may encourage a greater participation in ageing research, particularly in underprivileged communities, thus democratising access to scientific advancements in longevity studies.